Maximum fee vs. child benefit: a welfare analysis of Swedish child-care fee reform - Anna Brink; Katarina Nordblom; Roger Wahlberg (Institute for the Study of Labor (IZA), 2007)
The effects of a recent Swedish child-care fee reform are compared with those of an alternative reform, increased child benefits. The fee reform implied considerably decreased fees and was intended to increase both labor supply among parents and their economic well-being. We estimate labor supply effects using a discrete choice labor supply model, and simulate behavioral responses to the changes. We find positive, but small, effects on labor supply from reduced fees, while increased child benefits would make single mothers decrease their labor supply. On the other hand, increased child benefits would make income distribution more equal. We make a social welfare comparison and conclude that for plausible values of inequality aversion, the alternative reform would have been preferable to the implemented fee reform.
urn:nbn:de:101:1-20080402266
Keywords: 330; Kinderbetreuung; Familienleistungsausgleich; Arbeitsangebot; Einkommensverteilung; Schweden